Pemanfaatan Media Wordwall dalam Pembelajaran Fiqih: Tinjauan pada Pemahaman Siswa - Fadilatun Nikmah Simamora; Ali Jusri Pohan; Marlian Arif Nasution (Prodi Pendidikan Keagamaan Islam, 2025)
This study aims to describe the use of Wordwall media in Fiqh learning at MIS Model Mandailing Natal and to examine its effect on students’ understanding. This research employed a descriptive qualitative approach. Data were collected through observation, interviews, and documentation. The results indicate that Wordwall media was utilized as a means of material reinforcement and formative evaluation. Students’ understanding of Fiqh learning improved in four main aspects: conceptual, procedural, applicative, and rational. Furthermore, the use of Wordwall had a positive impact on students’ learning motivation, including increased interest, active participation, perseverance, learning readiness, and achievement orientation. Its strengths lie in being interactive and engaging, while its weaknesses include limited facilities and technological dependence.